Older adults and game-based systems: Engagement model and player types of characterization based on their motivations - Salazar-Cardona, Johnny (2024)
Older adults are now actively participating in game-based systems. They find in these technological solutions not only a form of entertainment and socialization, but also a way to stimulate themselves physically and cognitively. Although, their participation is increasing, they face challenges such as the digital divide, since most of the games are oriented to a young audience with different tastes and motivations. Therefore, although positive results are obtained in terms of participation, there is still potential for improvement, since current game experiences are not fully adapted to the tastes and needs of older adults. Consequently, the objective of this paper is to propose a characterization of the types of players in older adults, based on the motivations previously identified. This is to better understand this population and design more appropriate game experiences. It is hoped that from the results of this research it will be possible to create attractive and fun game environments for older adults, thus improving their experience as players in these systems.